Study Of MSQ As Low-K Dielectric Material For Semiconductor Devices - Wong, Man On (2006)
High spped performance in VLSI devices requires the use of semiconductor materials such as copper interconnects and low-k dielectric. Low-k dielectric can reduce the parasitic capacitance between two metal lines, which allows higher operational speed as compared to silicon oxide.